ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PELAPORAN KEUANGAN (Studi Empiris pada Perusahaan Otomotif dan Komponen yang terdaftar di BEI) - Lisa Alvionita; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2021)
This study aims to determine the factors that affect the timeliness of financial reporting on company performance. Empirical study on automotive and component companies listed on the Indonesia Stock Exchange 2016-2018. The sampling method used purposive sampling. The samples obtained in this study were 12 companies that had sample criteria. The analysis used in this research is Logistic Regression Analysis. The results of this study are that company size has a significant positive effect on the timeliness of financial reporting, managerial ownership as proxied by ROE has no effect on the timeliness of financial reporting, liquidity as proxied by Current Ratio has a significant effect on the timeliness of financial reporting, managerial ownership has a significant positive effect on accuracy financial reporting timeKeywords: Firm Size, Profitability, Liquidity, Managerial Ownership